Evaluation of oxidative stress levels using glutathione peroxidase (GPx) expression on hyperglycemia-induced rats testis - Andreas Pramudito; Sakti Ronggowardhana Brodjonegoro; Ahmad Zulfan; Aria Danurdoro; Didik Setyo Heriyanto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2021)
Diabetes mellitus (DM) is a global health problem with an estimated 422 million cases worldwide. Previous studies reported a correlation between hyperglycemia and oxidative stress‐related male infertility in DM. Glutathione peroxidase (GPx) can cause DNA damage due to oxidative reactions. Therefore, it could be used as potential indicator of antioxidant therapy. The study aimed to evaluate the expression level of GPx on the hyperglycemia-induced rats. This was an experimental case-control study using 27 Wistar rats divided into three groups i.e. hyperglycemia induction for four weeks group, eight weeks group, and a control group with no intervention. Following after induction, total RNA from the rats' testis was extracted, and GPx expression was analyzed using qPCR. Data were analyzed using SPSS, and a p <0.05 was considered significant. The study showed a significantly higher GPx mRNA expression level after hyperglycemia induction in both 4 and 8 weeks groups (16.93 ± 3.32 and 17.62 ± 3.42) compared to control group (9.94 ± 2.91) (p< 0.05). However, no significantly different between the 4 weeks group and 8 weeks group was observed (p >0.05). In conclusion, hyperglycemia increases GPx mRNA expression in rats. It may change the testicular environment's oxidative processes and impairs male reproductive function in the Sertoli cells with no exception.